Psychosis in a primary hyperparathyroidism patient with mild hypercalcemia: A case report. Issue 12 (26th March 2021) - Otsuki, Koji; Izuhara, Muneto; Miura, Shoko; Yamashita, Satoko; Nagahama, Michiharu; Hayashida, Maiko; Hashioka, Sadayuki; Miyaoka, Tsuyoshi; Hotta, Yukie; Shimizu, Yasuhiko; Inagaki, Masatoshi
Abstract: Introduction: Primary hyperparathyroidism (PHPT) is characterized by hypercalcemia and an elevated level of serum parathyroid hormone (PTH). PHPT presents with a complex set of renal, skeletal, and neuropsychological symptoms. Parathyroidectomy (PTX) is a radical treatment that is recommended for all physically symptomatic patients with PHPT. However, psychiatric symptoms are not considered as an indication for surgery. There remains an important issue from the view of perioperative management of whether PTX should be performed with the presence of uncontrolled psychiatric symptoms or deferred until severe psychiatric symptoms have been controlled. We report a case of mild hypercalcemia that caused severe psychosis in PHPT, which improved dramatically following PTX and resulted in successful postoperative management. Patient concern: Our patient was a 68-year-old Japanese woman. She was diagnosed with PHPT, which was triggered by mild hypercalcemia. She was due to receive an operation for osteoporosis and kidney stones. She had severe psychosis, despite medication. Blood examinations revealed mild hypercalcemia (10.4 mg/dL, 8.8–10.1 mg/dL) and elevated serum levels of intact PTH (184.0 pg/mL, 10–65 pg/mL). Diagnosis: She was diagnosed with severe psychosis caused by mild hypercalcemia in PHPT. Interventions: Although she was treated with 37.5 mg quetiapine and 2 mg risperidone daily, she was excessively sedated and rejected oral treatment. Therefore, we decided to perform the operation. Outcomes: Immediately following surgery, serum levels of calcium, and intact PTH were normalized. Her psychotic symptoms ceased completely 5 days after surgery. Conclusion: We emphasize that PHPT presents with various severe psychiatric symptoms, even in mild hypercalcemia. Psychiatric symptoms may be the only salient symptoms in PHPT, and thus clinicians should suspect PHPT in patients with psychiatric symptoms and mild hypercalcemia. Furthermore, PTX is recommended for PHPT—even in the presence of severe uncontrolled psychiatric symptoms, which carries risks for postoperative management—because psychiatric symptoms are expected to improve and good postoperative management is possible.